(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The research were conducted in the Carpathians and the adjacent areas during 2006-2012. The objects of naturе reserve fund of Ivano-Frankivsk region such as Carpathian National Nature Park, Halych National Nature Park, National Nature Park «Hutsulshchyna», Gorgany Nature Reserve were examined. 18 species of fungi of the genus Amanita Pers. are recorded. The systematical , ecological and phenological characteristics and distribution of studied species are given. One species, namely Amanita lividopallescens (Secr. ex Boud.) Kühner & Romagn., revealed for the first time in Ukraine. Amanita ceciliae (Berk. & Broome) Bas, Amanita franchetii (Boud.) Fayod, Amanita regalis (Fr.) Michael, Amanita strobiliformis (Paulet ex Vittad.) Bertill. should be considered regionally rare in the Carpathians. One species (Amanita solitaria Bull.: (Fr.) Mer.) is listed in the Red data book of Ukraine. Іn general, there are 20 species of the genus Amanita in the Ukrainian Carpathians.